2019
DOI: 10.1103/physrevresearch.1.033100
|View full text |Cite
|
Sign up to set email alerts
|

Local magnetic anisotropy by polarized neutron powder diffraction: Application of magnetically induced preferred crystallite orientation

Abstract: Polarized neutron diffraction allows to determine the local susceptibility tensor on the magnetic site both in single crystals and powders. It is widely used in the studies of single crystals, but it is still hardly applicable to a number of highly interesting powder materials, like molecular magnets or nanoscale systems because of the low luminosity of existing instruments and the absence of an appropriate data analysis software. We show that these difficulties can be overcome by using a large area detector i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…Recently, some of us have shown how polarized neutron diffraction (PND) from single crystals can provide accurate magnetic susceptibility tensors, clearly showing the direction and size of the easy axis of magnetization (Klahn et al, 2018;Ridier et al, 2016;Gukasov & Brown, 2002;Tripathi et al, 2021). Now, a potentially disruptive innovation allows similar information to be obtained from PND on powder (pPND) samples (Kibalin & Gukasov, 2019) and we present the first thorough analysis using this approach. In a parallel research path, we have recently shown how the d-orbital populations obtained from multipole modeling of single-crystal X-ray diffraction (Holladay et al, 1983) provide significant insight into the magnetic properties of transition-metal based SMMs (Craven et al, 2018;Thomsen et al, 2019;Bunting et al, 2018;Damgaard-Møller et al, 2020a,b,c).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some of us have shown how polarized neutron diffraction (PND) from single crystals can provide accurate magnetic susceptibility tensors, clearly showing the direction and size of the easy axis of magnetization (Klahn et al, 2018;Ridier et al, 2016;Gukasov & Brown, 2002;Tripathi et al, 2021). Now, a potentially disruptive innovation allows similar information to be obtained from PND on powder (pPND) samples (Kibalin & Gukasov, 2019) and we present the first thorough analysis using this approach. In a parallel research path, we have recently shown how the d-orbital populations obtained from multipole modeling of single-crystal X-ray diffraction (Holladay et al, 1983) provide significant insight into the magnetic properties of transition-metal based SMMs (Craven et al, 2018;Thomsen et al, 2019;Bunting et al, 2018;Damgaard-Møller et al, 2020a,b,c).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed description of the instrument scattering geometry and typical measurement conditions can be found in Ref. [32]. Initially the powder was introduced in a vanadium container of 6 mm diameter without compressing, and a powder diffraction diagram was collected at 5 K in zero field.…”
Section: Appendix A: Experimental Methodsmentioning
confidence: 99%
“…The tensor, which describes the anisotropy on the rare-earth ion, can be determined by 2D Rietveld refinement of the diffraction patterns. Refinements were performed with the newly developed RHOHI program [32] . More experimental details can be found in Appendix A.…”
Section: A Polarized Neutron Powder Diffractionmentioning
confidence: 99%
See 2 more Smart Citations